Pavilion of Knowledge – Ciência Viva Centre, Lisbon. Portugal - Sequeira, Marta (TC Cuadernos, 2022)
The Pavilion of Sea Knowledge was planned for a site between Alameda Central and Doca dos Olivais in the context of the Lisbon International Exhibition in 1998. At the time, the urban plan where it was to be located had been stabilised, but the configuration and image of the surrounding buildings were still unknown. From the outset, the idea was to design a building that could constitute a counterpoint to a predictably saturated environment. One of the most intriguing aspects of the challenge was the fact that this building would be dedicated to the knowledge of the seas, but was, a!er all, far from the water. In a first version of the project, a kind of periscope was proposed – a large semi-dark central void that would house large reproductions of various boats and which would be illuminated by a large mirror placed on the ceiling, which would reflect the fluctuation of the water of the large basin of the Tagus River estuary inside the space, converting it into the real construction material of the building.